2017
DOI: 10.5114/ceji.2017.67319
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of inflammatory cytokines and oxidative stress markers in prostate cancer patients undergoing curative radiotherapy

Abstract: Prostate cancer is the second leading cause of cancer-related death in men. The present study was carried out to investigate the radiation response of serum cytokines and oxidative markers to find out if these novel biomarkers have significant applications regarding radiation outcome in prostate cancer patients. Significant elevations of prostatic specific antigen (PSA), asymmetric dimethyl arginine (ADMA) and nitric oxide (NO) were recorded in cancer prostate patients at the time of diagnosis compared to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In addition, the mRNA and protein expressions of SERPINB2 in CNE2R cells in our study were determined to be significantly lower than those in CNE2 cells, which was consistent with the findings of Li XH et al [22]. Mounting data has shown that radiotherapy can induce the release of inflammatory cytokines and oxidative stress markers, and these mediators can lead to the significant upregulation of SERPINB2 in multiple cells [35, 36]. More importantly, evidence has confirmed a high correlation between SERPINB2 and EMT alteration in cells; for example, the absence of SERPINB2 enhanced cell migration via regulating EMT in tumor cells, as indicated by Longhin E et al [37].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the mRNA and protein expressions of SERPINB2 in CNE2R cells in our study were determined to be significantly lower than those in CNE2 cells, which was consistent with the findings of Li XH et al [22]. Mounting data has shown that radiotherapy can induce the release of inflammatory cytokines and oxidative stress markers, and these mediators can lead to the significant upregulation of SERPINB2 in multiple cells [35, 36]. More importantly, evidence has confirmed a high correlation between SERPINB2 and EMT alteration in cells; for example, the absence of SERPINB2 enhanced cell migration via regulating EMT in tumor cells, as indicated by Longhin E et al [37].…”
Section: Discussionsupporting
confidence: 91%
“…IL-4 is a pleiotropic cytokine that is mainly produced by activated Th2 cells, mast cells, and basophils. It has been shown that the levels of IL-4 increases post-irradiation in patients with prostate cancer, and has been implicated in radiation-induced fibrosis [ 75 , 76 ]. Similar to our results, cereal fiber has been shown to decrease the levels of IL-4 in the sera of healthy persons [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…This highly unpredictable mechanism renders the treatment less effective and frequently causes recurrence after radical RT—up to one-third of PCa patients experience biochemical failure after RT [ 2 ]. Despite identifying several molecular mechanisms associated with radioresistance, the ability to predict an individual PCa patient’s response to RT is still limited and based mostly on the pretreatment assessment of prostate specific antigen (PSA), tumor stage and Gleason score [ 3 , 4 ]. Therefore, there is a need to identify new biomarkers that could more accurately predict response to RT.…”
Section: Introductionmentioning
confidence: 99%